Evaluative Analysis of The Implementation “Merdeka Belajar-Kampus Merdeka” (MBKM) Curriculum in Arabic Language Education Programs - Mohammad Zaelani Musonif; Kholisin Kholisin; Hanik Mahliatussikah; Ziad Abdulrazzaq Esmael (PPPBA, 2024)
This research aims to evaluate the implementation of the Merdeka Belajar-Kampus Merdeka (MBKM) curriculum in the Arabic Language Education study program in Indonesia. The study utilizes an evaluative research approach to provide critical insights into the effectiveness and challenges of implementing the MBKM curriculum. Data is gathered through a qualitative method, primarily focusing on literature review techniques. The research findings shed light on the dual implementation of the MBKM curriculum within and outside the study program. Specifically, the MBKM curriculum in the Arabic Language Education study program is implemented with a 5-1-2 format. The evaluation highlights certain considerations for the MBKM curriculum in the Arabic Language Education study program. These considerations include addressing the misalignment of course equivalencies or conversions with the MBKM program chosen by students, addressing dual curriculum programs, and mitigating biases in focus areas of study and graduate competencies. Additionally, attention is drawn to the pedagogical competencies that need to be emphasized for non-education students participating in the Teaching Assistance program within Educational Units. Furthermore, the research identifies potential challenges related to internship programs, emphasizing the importance of avoiding creating a cheap workforce that only adheres to industrial logic.